The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/gim.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratories collaborate to resolve differences in variant interpretations submitted to ClinVar

Abstract: Purpose Data sharing through ClinVar offers a unique opportunity to identify interpretation differences between laboratories. As part of a ClinGen initiative, four clinical laboratories (Ambry, GeneDx, Partners Healthcare Laboratory for Molecular Medicine, and University of Chicago Genetic Services Laboratory) collaborated to identify the basis of interpretation differences and to investigate if data sharing and reassessment resolves interpretation differences by analyzing a subset of variants. Methods ClinV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
258
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(271 citation statements)
references
References 18 publications
9
258
0
Order By: Relevance
“…Answering this question is a central challenge because it is clear that clinical laboratories are currently having trouble with using functional data to agree on variant interpretations. 80 The large scale of MAVE data provides several key advantages that could help alleviate the problematic nature of using functional data for interpretation. First, all variants within a MAVE are tested simultaneously so that measurements for different variants are readily comparable to each other, whereas one-at-atime assays are performed by different personnel in different research labs at different times.…”
Section: Limitations Of Maves and How To Overcome Themmentioning
confidence: 99%
“…Answering this question is a central challenge because it is clear that clinical laboratories are currently having trouble with using functional data to agree on variant interpretations. 80 The large scale of MAVE data provides several key advantages that could help alleviate the problematic nature of using functional data for interpretation. First, all variants within a MAVE are tested simultaneously so that measurements for different variants are readily comparable to each other, whereas one-at-atime assays are performed by different personnel in different research labs at different times.…”
Section: Limitations Of Maves and How To Overcome Themmentioning
confidence: 99%
“…However, NGS also yields increasing numbers of variants that predominantly are of unknown significance and compounds the challenge of variant interpretation (Good, Ainscough, McMichael, Su, & Griffith, 2014; Kamps et al., 2017). As clinical analysis of large volumes of patient variant data becomes increasingly difficult, inconsistencies increase both in variant interpretation and reporting between laboratories (Harrison et al., 2017). This issue is compounded by propagation of these inconsistencies to widely accessed knowledgebases (Hoskinson, Dubuc, & Mason‐Suares, 2017; Yorczyk, Robinson, & Ross, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In many of the instances of discrepancies in assertion, consensus has been achieved simply by sharing evidence previously unavailable to one party 79 . Harrison et al found that 87.2% of discordant variants were resolved by reassessment and data sharing 8 . Several initiatives 5, 10– 14 have had success in encouraging the public sharing of datasets and new studies, but for the foreseeable future, private data will continue to be a challenge to achieving consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in the field of cardiovascular disease, there have been several high-profile instances of cardiovascular variants deemed to be highly pathogenic, yet not segregating with disease 9, 16, 17 . This unfortunate outcome is inevitable owing to the aforementioned reasons and illustrates a key issue: the continual need to share and reconcile new information with old data and reclassify clinical assertions as appropriate on a regular basis 6, 8 .…”
Section: Introductionmentioning
confidence: 99%